REVERSE MAGIC STRENGTH OF FESTOON TREES - Basha, S. Sharief; Reddy, K. Madhusudhan (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we prove that the reverse super edge-magic strength of some diﬀerent festoon trees.